The relationship between System of classification, Selection of symbols, And system of prohibitions. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Key words: System of classification, Selection of Symbols, System of Prohibitions.